PENGARUH LEVERAGE (DER), RETURN ON ASSETS (ROA), RASIO LANCAR (CR), TERHADAP HARGA SAHAM PADA SEKTOR TRADE, SERVICE & INVESTMENT DI BURSA EFEK INDONESIA PERIODE 2015-2018 - Natalia Sabrina Togatorop; Kurnia Sari Siregar; Maya Agustina Tanjung; Keisafan Hulu (JURNAL GLOBAL MANAJEMEN, 2019)
This research aims at testing and analyzing how the effect of Leverage (DER), Return On Asset (ROA), Current Ratio (CR)on stock price in Trade Service &Investmentcompanies registered in Indonesia Stock Exchange for 2015 – 2017 period. Research method used is qualitative approach and the type of research is quantitative descriptive in which the nature of this research is explanatory. The total population of this research is 132 Trade Service & Investmentcompanies. Samples of this research are as many as 41 Trade Service & Investmentcompanies that have met the criteria. Data analysis was done by using multiple linear regression analysis with classical assumption test. Research findings show that: 1)Leverage (DER), Return On Asset (ROA), Current Ratio (CR) simultaneously affect significantly on stock price of Trade Service & Investmentcompanies registered in Indonesia Stock Exchange for 2015 – 2017 period with the result Ftest ≥ Ftable or significant 6.934 ≥ 2.66 and 0.000 ≤ 0,05; 2) Partially, Leverage has no effect and insignificant on stock price; 3) Current Ratio (CR) does not affect and insignificant on stock price. From the results of the coefficient of determination analysis, the value of AdjustedR2shows that the variety of stock price variety that can be explained by Leverage (DER) variable, Return On Asset (ROA) is as many as 0.098 or is 9.8% meanwhile the rest is as many as 90.2% that can be explained by other variable variations.